2022
DOI: 10.1099/mgen.0.000763
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of ocular Streptococcus pneumoniae is highly diverse and formed by lineages that escape current vaccines

Abstract: Streptococcus pneumoniae is a leading cause of ocular infections including serious and sight-threatening conditions. The use of pneumococcal conjugate vaccines (PCV) has substantially reduced the incidence of pneumonia and invasive pneumococcal diseases, but has had limited impact on ocular infections. Additionally, widespread vaccine use has resulted in ongoing selective pressure and serotype replacement in carriage and disease. To gain insight into the population stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…S. pneumoniae consists of many serotypes, which differ in their tropism and infectivity of different tissues. Interestingly, an epidemiologic study at Massachusetts Eye and Ear Institute found that 95% of S. pneumoniae keratitis isolates are encapsulated, whereas 80% of conjunctivitis isolates are unencapsulated 37 . While polysaccharide capsule may not be an essential virulence factor for S. pneumoniae keratitis 58,59 the ongoing selective pressure of widely used vaccines targeting a small number of capsule serotypes has resulted in the emergence of novel serotypes not covered by these vaccines, which are becoming common colonizers of the nasopharynx and seem to be well adapted to cause keratitis 37 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S. pneumoniae consists of many serotypes, which differ in their tropism and infectivity of different tissues. Interestingly, an epidemiologic study at Massachusetts Eye and Ear Institute found that 95% of S. pneumoniae keratitis isolates are encapsulated, whereas 80% of conjunctivitis isolates are unencapsulated 37 . While polysaccharide capsule may not be an essential virulence factor for S. pneumoniae keratitis 58,59 the ongoing selective pressure of widely used vaccines targeting a small number of capsule serotypes has resulted in the emergence of novel serotypes not covered by these vaccines, which are becoming common colonizers of the nasopharynx and seem to be well adapted to cause keratitis 37 …”
Section: Resultsmentioning
confidence: 99%
“…37 While polysaccharide capsule may not be an essential virulence factor for S. pneumoniae keratitis 58,59 the ongoing selective pressure of widely used vaccines targeting a small number of capsule serotypes has resulted in the emergence of novel serotypes not covered by these vaccines, which are becoming common colonizers of the nasopharynx and seem to be well adapted to cause keratitis. 37 We, therefore, examined if 2-O-sulfated heparan compounds also inhibit corneal infection by other serotypes of S. pneumoniae, including the emerging serotype 35B. Injured mouse corneas were topically infected with IDI30/44 (serotype 35B), a clinical keratitis isolate, or with L82016 (serotype 6B) and NDS-HP, 2ODS-HP, H, NS-H, or NS2OS-H and the corneal bacterial burden was enumerated at 6 h pi.…”
Section: -O-sulfated Hs Domains Inhibit S Pneumoniae Corneal Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activity of MSlys was tested against ocular S. pneumoniae isolates (n=31) molecularly characterized in our previous studies 5,6 . Protocols for J o u r n a l P r e -p r o o f obtaining discarded isolates were approved by the Mass General Brigham Institutional Review Board, and the study was conducted in accordance with the Declaration of Helsinki.…”
mentioning
confidence: 99%